Inventory of Bivalve in the Coastal Area of Desa Sungai Nibung West Kalimantan - Ikha Safitri; Arie A. Kushadiwijayanto; Sy. Irwan Nurdiansyah; Mega Sari Juane Sofiana; Warsidah Warsidah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Desa Sungai Nibung, Kubu Raya Regency, has been designated as one of the conservation areas in West Kalimantan. The coastal area of this village has potential of natural resources with a high level of diversity, including bivalves. Local community catch and sell bivalves for consumption. It is due to their high nutritional content, so that they are used by the local community as food and a source of protein. Inventory of biota is the first step to manage biological resources and support the management plan for a conservation area in this village. The study aimed to determine the diversity of bivalves in the coast of Desa Sungai Nibung, West Kalimantan. The research was conducted in December 2022. Sample collection was done using an exploratory method. Bivalves were taken, then stored in the cooling box for further identification. The result showed three bivalve species, such as Polymesoda erosa, Anadara granosa, and A. antiquata.